Teacher Learning Strategies in Overcoming Student Boredom in Tahfis Subjects at SMP Muhammadiyah 8 Medan - Emia Pepayosa (AR-RASYID : Jurnal Pendidikan Agama Islam, 2023)
Tahfidz learning is religious-based learning as a means of education for Muslims to memorize the Al-Qur'an. Memorizing short letters really needs to be implemented in junior high school, so that a strong faith is embedded in the child's soul, encouraged to learn to obey the rules of Allah's Shari'ah and then be able to practice them in accordance with Allah's Shari'a. This research uses a qualitative approach. Data collection uses documentation techniques, while data analysis techniques use qualitative descriptive analysis techniques.